2015
DOI: 10.1063/1.4917418
|View full text |Cite
|
Sign up to set email alerts
|

Proposed linear energy transfer areal detector for protons using radiochromic film

Abstract: Radiation therapy depends on predictably and reliably delivering dose to tumors and sparing normal tissues. Protons with kinetic energy of a few hundred MeV can selectively deposit dose to deep seated tumors without an exit dose, unlike x-rays. The better dose distribution is attributed to a phenomenon known as the Bragg peak. The Bragg peak is due to relatively high energy deposition within a given distance or high Linear Energy Transfer (LET). In addition, biological response to radiation depends on the dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Radiochromic film can be used as a reference dosimeter for biomedical experiments with low-energy proton beams if appropriate LET corrections are applied [36]. There are numerous researchers re-ported that under-response of radiochromic film in the presence of proton SOBPs which could be defined as “quenching effect” of the dosimeter in the region [2633,3537]. “Quenching” is said to occur when, for a given physical dose, a dosimeter not limited to radiochromic film gives a lower output reading for radiation with high LET than for the same dose of low LET radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiochromic film can be used as a reference dosimeter for biomedical experiments with low-energy proton beams if appropriate LET corrections are applied [36]. There are numerous researchers re-ported that under-response of radiochromic film in the presence of proton SOBPs which could be defined as “quenching effect” of the dosimeter in the region [2633,3537]. “Quenching” is said to occur when, for a given physical dose, a dosimeter not limited to radiochromic film gives a lower output reading for radiation with high LET than for the same dose of low LET radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Calibration films were irradiated at 18, 20, and 23 cm while the chamber array was irradiated at nearly identical depths of 18, 20 and 24 cm. The LET dependence of radiochromic films has been thoroughly investigated [6,18,22,2633] and it has been established that the effect is highest for lower (< 11 MeV) proton energies [28]. However, for spot scanning beams, there may be a larger distribution of energies used to irradiate the PTV which could make accounting for LET corrections quite variable.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, many methods for LET measurements had been developed using different detectors, including dual ionization chambers (Tegami et al 2017), thermoluminescence detector (TLD) (Parisi et al 2019, Shimomura et al 2020, CR-39 (Hirano et al 2018), radiographic films (Mayer et al 2015), gel dosimeters (Maeyama et al 2015), optically stimulated luminescence dosimeters (OSLD) (Granville et al 2014a, 2014b, Christensen et al 2022, tissue equivalent proportional counter (Bianchi et al 2020), silicon on insulator dosimeter (Chacon et al 2020, Samnøy et al 2020, James et al 2021, Lee et al 2021 and so on. As most of these methods were still in the experimental exploration, few comparative studies between methods had been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Their method does not measure LET directly using its physics definition instead measures the ratio of ultraviolet to blue emission intensities as a surrogate of LET, and uses MC simulations to establish a relationship between the surrogate parameter and LET. A few other methods are available for proton LET measurement, [10][11][12][13][14][15] but all similarly employ surrogates and require MC simulations to calibrate the surrogates and LETs.Lineal energy,the energy imparted at each event in a volume of interest divided by the mean chord length in that volume, 16 is another surrogate of LET and can be measured with microdosimeters. 17,18 MC has been used to simulate the energy-dependent mean chord length in the detector sensitive volume.…”
Section: Introductionmentioning
confidence: 99%